First Report of Passiflora latent virus in Passion fruit (Passiflora edulis) in China - Bao, Sarina; Ge, FangYe; Li, XiangYing; Bo, Bo (Plant disease, 2023)
Passion fruit (Passilora edulis, family Passifloraceae.) is an economically important fruit crop in many tropical and subtropical regions worldwide. It is widely planting in southern China, and in greenhouses throughout the country. In Mar 2022, symptoms of a viral-like infection were observed on the leaves of passion fruit plants in a 3-hectare greenhouse complex in Hohhot, China. Chlorotic lesions were observed on leaves of two vines of passion fruit and symptomatic leaves developed chlorotic spots, followed by systemic leaf chlorosis and necrosis. Dark ringed spots emerged on the surface of matured fruits (Figure 1). To confirm infectivity, mechanical transmission of the virus was performed by grinding leaves from two symptomatic passion fruit vines in 0.1M phosphate buffer pH 7, and the resulting two samples were each used to rub-inoculate carborundum-dusted leaves of three healthy passion fruit seedlings. Newly emerging leaves of inoculated plants developed mild mosaic symptoms 30-days after inoculation. Three samples from each of the two original symptomatic plants and two samples from each inoculated seedling tested positive using a Passiflora latent virus (PLV) ELISA Kit (Creative Diagnostics, USA). To further confirm the virus identity, total RNA from leaf samples from one of the original greenhouse symptomatic plants and one of the inoculated seedlings were extracted using an TaKaRa MiniBEST Viral RNA Extraction Kit (Takara, Japan). The two RNA samples were subjected to reverse transcription-polymerase chain reaction (RT-PCR) tests with virus specific primers PLV-F (5'-ACACAAAACTGCGTGTTGGA-3') and PLV-R (5'-CAAGACCCACCTACCTCAGTGTG-3') (Cho et al., 2020). RT-PCR products of the expected 571 bp were obtained from both the original greenhouse sample and inoculated seedling. Amplicons were cloned into the pGEM-T Easy Vector, and two clones per sample were Sanger sequenced bidirectionally (Sangon Biotech, China), and the sequence of one clone from one of the original symptomatic sample was uploaded to NCBI (GenBank OP320922.1). This accession had 98% nucleotide sequence identity with a PLV isolate from Korea (GenBank: LC556232.1). RNA extracts from two asymptomatic samples tested negative for PLV with both ELISA and RT-PCR tests. We also tested the original symptomatic sample for common occurring passion fruit viruses, including passion fruit woodiness virus (PWV), cucumber mosaic virus (CMV), east asian passiflora virus (EAPV), telosma mosaic virus (TeMV), papaya leaf curl Guangdong virus (PaLCuGdV), and the RT-PCR results were negative for those viruses. However, based on the systemic leaf chlorosis and necrosis symptoms, we cannot preclude a mixed infestation of other viruses. PLV affects fruit quality and has high potential to reduce market value. To our knowledge, this is the first report of PLV in China, which could provide a reference basis to PLV identification, prevention and control. Acknowledgments This research was carried out with the support of Inner Mongolia Normal University High-level Talents Scientific Research Startup Project (Grant no. 2020YJRC010). Supplementary material Figure 1. Mottle, leaf distortion, puckering symptoms on old leaf (A), mild puckering symptom on young leaf (B), and ring-striped spots symptoms on fruit (C) of the PLV infected passion fruit plant in China.